Carbon and Oxygen Isotope Composition in Soil Carbon Dioxide and Free Oxygen within Deep Ultisols at the Calhoun CZO, South Carolina, USA. Issue 5 (19th November 2018) - Cherkinsky, Alexander; Brecheisen, Zachary; Richter, Daniel
ABSTRACT: In order to evaluate effects of three land uses on isotopic compositions of CO2 and O2 of soil air to 5 m soil depth, a field study was conducted in the Calhoun Critical Zone Observatory, located in the subtropical climate of the Southern Piedmont of South Carolina, USA. Soil gas reservoirs were installed in ecosystems with three different land uses, each replicated three times: (i) reference hardwood stands that were never cultivated; (ii) currently cultivated plots; (iii) pine stands, which had been used for growing cotton in 19th century but were abandoned in about the 1930s and 1940s when they were regenerated with pines that are today 70–80 yr old. In addition to soil CO2 and O2 concentration measurements, soil gas samples were analyzed for Δ 14 C, δ 13 C, and δ 18 O. Stable carbon isotopic composition becomes lighter with the depth in soils of all three land uses: in the cultivated site δ 13 C decreases from –18‰ at 0.5 m to –21‰ at 5 m, in pine site from –22 to –25‰, and in hardwood from –21.5 to –24.5‰, respectively. Δ 14 C increased with depth from 40 to 60‰ in the top 0.5 m to about 80–140‰ at 5 m depending on land use. While surficial soils had relatively similar Δ 14 C in CO2, between 40 to 60‰ at 0.5 m, at 3 and 5 m, cultivated soils had the highest Δ 14 C, hardwood the lowest, and pine in between, a pattern that emphasizes the importance of contemporary respired CO2 in hardwood stands. Oxygen isotopic composition of CO2 did not change with depth, whereas free O2 was greatly enriched in lower horizons of forest soils, which we attribute to strong fractionation by respiration.